Representations of native and foreign language lexical equivalents in the mental lexicon of foreign language learners - Vilke-Pinter, Dubravka (Array, 2008)
This paper addresses the question of how native (L1) and foreign (L2) language lexicons are represented and processed in the mind of a foreign language learner. Semantic differential technique, measuring connotative meaning of the words has been used to investigate the relationship between the representations of the corresponding L1 and L2 words in bilinguals’ mental lexicon. Two groups of 60 L1 Croatian speakers, of high and medium L2 (english) proficiency, judged sets of corresponding L1 and L2 words, emotionally saturated (coloured) and neutral ones (home, family, justice, pencil, glass) against a 14 bipolar 7 point scale (bad - good, ugly - beautiful, pleasant - unpleasant). Mean profiles of the corresponding words were calculated to indicate the allocated meanings. The results are discussed within the context of conceptual mediation vs. lexical association debate, and in light of the Paradis’ Integrated Model of Neurolinguistic Organisation, namely Three store hypothesis, according to which mental representations at the cognitive level are organized slightly differently by each of the speaker' s languages, as on the one hand each language imposes its own structure on the conceptual field grouping only those attributes that are semanticlly relevant, and on the other reflects a particular organization of speaker's experiences. The results obtained suggest that in respect to some dimensions of meaning, irrespective of their level of L2 proficiency, speakers tend to allocate different values to the corresponding L1 and L2 words that are emotionally coloured.